Physical activity and body mass index among women who have experienced infertility - Esmaeilzadeh, Seddigheh (Termedia Publishing House, 2013)
INTRODUCTION: The experience of infertility is a common medical condition in the developing countries. The aim of this retrospective epidemiologic study was to determine fertility status and parity in Babol, Iran and then identify physical activity and body mass index (BMI) among women who have experienced infertility. MATERIAL AND METHODS: A total of 1,081 women aged 20-45 years were selected using cluster sampling. The current physical activity was measured using the original International Physical Activity Questionnaire short form. Lifestyle factors were compared between those who had experienced infertility (n = 168) and the rest of the women. A face-to-face household interview was conducted using a specially designed interview questionnaire. RESULTS: After adjusting for suspected confounding factors, women with infertility experience had a 4.8-fold increased risk of obesity (OR = 2.02, CI = 0.70, 5.84) and almost a 3.8-fold increased risk of being overweight (OR = 2.11, CI = 0.72, 6.17) compared to women without infertility. No significant differences were found in Met-minutes of sedentary activity, intensity of walking, moderate, vigorous, and total physical activity, self-reported dietary intake, exercise, and level of physical activity between women with and without experience of infertility. CONCLUSIONS: Since both obesity and infertility are increasing public health issues in Iranian women, more attention should be paid to lifestyle behaviors, especially gaining weight in women who have experienced infertility.